Immunology by numbers: quantitation of antigen presentation completes the quantitative milieu of systems immunology!. (June 2016) - Purcell, Anthony W; Croft, Nathan P; Tscharke, David C
Highlights: Epitope quantitation is critical for vaccine design and immunotherapy. MS approaches are a more comprehensive and accurate readout of antigen presentation. Approaches range from unbiased quantitative MS through to sensitive targeted MRM-MS. The quantitation of a large proportion of the immunopeptidome is within our grasp. Abstract : We review approaches to quantitate antigen presentation using a variety of biological and biochemical readouts and highlight the emerging role of mass spectrometry (MS) in defining and quantifying MHC-bound peptides presented at the cell surface. The combination of high mass accuracy in the determination of the molecular weight of the intact peptide of interest and its signature pattern of fragmentation during tandem MS provide an unambiguous and definitive identification. This is in contrast to the potential receptor cross-reactivity towards closely related peptides and variable dose responsiveness seen in biological readouts. In addition, we gaze into the not too distant future where big data approaches in MS can be accommodated to quantify whole immunopeptidomes both in vitro and in vivo .